Internalized stigma as an independent risk factor for substance use problems among primary care patients: Rationale and preliminary support - Kulesza, Magdalena (Drug Alcohol Depend, 2017)
BACKGROUND: Little is known about internalized stigma among primary care patients, and whether the presence of internalized stigma is related to the severity of substance use problems independent of substance use-related variables. We sought to examine the relationship between internalized stigma and substance use problems among primary care patients with opioid or alcohol use disorders (OAUDs). METHODS: We present baseline data from 393 primary care patients who were enrolled in a study of collaborative care for OAUDs. Regression analyses examined the relationship between internalized stigma and substance use problems, controlling for demographics, psychiatric comorbidity, and quantity/frequency of use. RESULTS: The majority of participants reported thinking, at least sometimes, that they “have permanently screwed up” their lives (60%), and felt “ashamed” (60%), and “out of place in the world” (51%) as a result of their opioid or alcohol use. Higher internalized stigma was significantly related to more substance use problems (β = 2.68, p<0.01), even after the effects of covariates were accounted for. Stigma added 22%, out of 51% total variance explained, leading to a significant improvement in prediction of substance use problems. CONCLUSIONS: Among this group of primary care patients with OAUDs, rates of internalized stigma were comparable to those reported in specialty substance use treatment settings. Consistent with extant specialty care literature, our results suggest that internalized stigma may be a unique contributor that is associated with treatment outcomes, such as substance use problems, among primary care patients with OAUDs.